The offset codebook (OCB) block cipher mode of operation for authenticated encryption. Issue 2 (4th March 2018) - Stallings, William
ABSTRACT: This article presents an overview of the concepts of and motivation for the OCB block cipher mode of operation. OCB is well suited for IoT, wireless, and other constrained devices where processing time and energy consumption are design issues. The article describes two versions of the OCB algorithm (OCB1 and OCB3) that have been widely accepted.